METHODOLOGY OF ENGLISH LANGUAGE TEACHING TO STUDENTS IN NON-PHILOLOGICAL EDUCATION WITH THE HELP OF INFORMATION TECHNOLOGIES - Rakhmatullaeva, Shakhnoza (Журнал иностранных языков и лингвистики, 2022)
This article is devoted to the issues of methodology of teaching English to students of non-philological Education. This Article discusses using Information Technologies as the important source in teaching Foreign Languages.